Balancing the piezoelectric coefficient and carrier concentration of Bi2WO6−x for ultrahigh piezocatalysis - Ying Wang; Xiaoli Xu; Lingbo Xiao; Lutao Li; Qiuhua Xu; Zhenhai Wen; Laishun Qin; Yanmin Jia; Dong-Liang Peng; Wanping Chen; Da Chen (Journal of Advanced Ceramics, 2024)
Balancing the piezoelectric coefficient and carrier concentration of materials is key in the field of piezocatalysis. In this work, Bi2WO6 material with both piezoelectric and semiconductor properties was chosen as a model material. A one-step ethylene glycol (EG)-assisted solvothermal method was used to synthesize Bi2WO6 with oxygen vacancies. By controlling the solvothermal time and temperature, the oxygen vacancy concentration (COV) was regulated. As COV increases, the piezoelectric coefficient decreases, the carrier concentration increases, and the hydrogen production rate first increases but then decreases. When COV reaches 1.45×1012 spins·mg−1, the corresponding piezoelectric coefficient and carrier concentration are 13.9 pm·V−1 and 2.90×1020 cm−3, respectively. The optimal hydrogen production rate per power of 2.21 μmol·g−1·h−1·W−1 is equivalent to or even better than that of most reported piezocatalysts. The piezoelectric coefficient and carrier concentration, as two factors, jointly determine the piezocatalytic performance. The findings of this research can provide important and deep-seated insights for better piezocatalysts in the future.